Cardiac parasympathetic outflow during dynamic exercise in humans estimated from power spectral analysis of P–P interval variability. Issue 3 (9th February 2016) - Takahashi, Makoto; Nakamoto, Tomoko; Matsukawa, Kanji; Ishii, Kei; Watanabe, Tae; Sekikawa, Kiyokazu; Hamada, Hironobu
Abstract : New Findings: What is the central question of this study? Should we use the high‐frequency (HF) component of P–P interval as an index of cardiac parasympathetic nerve activity during moderate exercise? What is the main finding and its importance? The HF component of P–P interval variability remained even at a heart rate of 120–140 beats min −1 and was further reduced by atropine, indicating incomplete cardiac vagal withdrawal during moderate exercise. The HF component of R–R interval is invalid as an estimate of cardiac parasympathetic outflow during moderate exercise; instead, the HF component of P–P interval variability should be used. The high‐frequency (HF) component of R–R interval variability has been widely used as an indirect estimate of cardiac parasympathetic (vagal) outflow to the sino‐atrial node of the heart. However, we have recently found that the variability of the R–R interval becomes much smaller during dynamic exercise than that of the P–P interval above a heart rate (HR) of ∼100 beats min −1 . We hypothesized that cardiac parasympathetic outflow during dynamic exercise with a higher intensity may be better estimated using the HF component of P–P interval variability. To test this hypothesis, the HF components of both P–P and R–R interval variability were analysed using a Wavelet transform during dynamic exercise. Twelve subjects performed ergometer exercise to increase HR from the baseline of 69 ± 3 beats min −1 to three different levels of 100, 120 and 140 beats min −1 . We also examined the effect of atropine sulfate on the HF components in eight of the 12 subjects during exercise at an HR of 140 beats min −1 . The HF component of P–P interval variability was significantly greater than that of R–R interval variability during exercise, especially at the HRs of 120 and 140 beats min −1 . The HF component of P–P interval variability was more reduced by atropine than that of R–R interval variability. We conclude that cardiac parasympathetic outflow to the sino‐atrial node can be estimated better by the HF component of P–P interval variability during exercise and that cardiac parasympathetic nerve activity exists during moderate dynamic exercise. Abstract :